Effect of periodontal therapy on metabolic control and levels of IL-6 in the gingival crevicular fluid in type 2 diabetes mellitus - Gabriela Alessandra da Cruz Galhardo Camargo; Meyriane de Andrade Lima; Tânia Vieira Fortes; Cristiane Salgado de Souza; Amélia Maria de Jesus; Roque Pacheco de Almeida (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this study was to compare the efficacy of metabolic control and levels of interleukin 6 (IL-6) in gingival crevicular fluid after periodontal therapy in type 2 diabetes mellitus (DM) and nondiabetic (NDM) patients. Methods: This study was performed in 20 subjects (10 type 2 DM and 10 NDM patients with generalized chronic periodontal disease. Both groups were recorded for clinical parameters (plaque index (PI), gingival index (GI), probing depth (PD), gingival recession (GR) and clinical attachment level (CAL)), metabolic control (fasting glucose levels, glycated a-hemoglobin (HbA1c), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides (TR)), and IL-6 levels at baseline and 3 months after periodontal treatment. Results: DM and NDM patients revealed significant statistical reductions for clinical parameters (P < 0.05, RM ANOVA) after 3 months. DM group had improvements on HbA1c and had significant statistical increased of TRG (P < 0.05, RM ANOVA) after 3 months. No differences of LDL/HDL and IL-6 levels were found after 3 months in both groups. Conclusion: DM group presented a significant reduction of HbA1c levels after periodontal therapy. However, TRG levels increased after 3 months, which suggest more confirmatory studies to investigate if these results will be repeated in other studies.